If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 2x + -4 = 3x + 2 Reorder the terms: 10 + -4 + 2x = 3x + 2 Combine like terms: 10 + -4 = 6 6 + 2x = 3x + 2 Reorder the terms: 6 + 2x = 2 + 3x Solving 6 + 2x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 2x + -3x = 2 + 3x + -3x Combine like terms: 2x + -3x = -1x 6 + -1x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -1x = 2 + 0 6 + -1x = 2 Add '-6' to each side of the equation. 6 + -6 + -1x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 2 + -6 -1x = 2 + -6 Combine like terms: 2 + -6 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 10x-124=97-3x | | 3/u=27/162 | | 2=-8y+2 | | 7.91=2 | | 16=7-3x | | 52=4v | | 3(3+4)=21 | | -13+2x+10=x+7 | | 7n-12=6 | | x+6/10+x-4/15=x+2/5 | | -3(a+2)-(a-6)=20 | | X-2/20=9/5 | | 3x^(4/3)+5x^(2/3)-2=0 | | b^2+8b-57=6 | | 1/-3=27 | | 7x+2=-9 | | 2w+6=52 | | 2x+22+14=14 | | 2x^2-4x=x^2+4x-1 | | 32/7+51/4-11/14 | | 7-7x+4x=-11 | | 3-1/5e=-7 | | U/-6+7=11 | | n+6=3n-10 | | y/4+2=c | | 3(x+4)=6+3x | | 27/10*10 | | x-8=r | | (8x^2+6x-5)-(6x^2+2)= | | 6x-32=3x+3 | | x-5=13-3x | | f(x)=4x+9x-1 |